ANALISIS BRAND SWITCHING PENGGUNA TRANSPORTASI ONLINE GOJEK DENGAN METODE MARKOV CHAIN DI KOTA BANDAR LAMPUNG - Arpan, Yunada; Dewi, Paulina Citra (Valid Jurnal Ilmiah, 2018)
This study aims to measure the magnitude of the percentage of users movement from online transportion of Gojek to other online transportation at the Community of Bandar Lampung City. This type of research uses descriptive research that describes the percentage of consumer displacement. The data used in this study is the primary data through the distribution of questionnaires to users who have used the Online Transportion Service of Gojek. Data analysis technique used was markov chain. From 44 respondents who use online transportation of Gojek, as many as 22 respondents are still using online transportation of Gojek, 19 respondents moved to online transportation of Grab and 3 respondents move to other online transportation. From the 42 respondents using Grab's online transportation, 12 were transferred to Gojek's online transportation, and 27 respondents continued to use Grab's online transport and 3 respondents moved to other online transport.14 respondents using other online transportation, as many as 6 respondents moved to Gojek's online transportation, one respondent moved to Grab's, and 7 respondents chose to keep using other branded online transportation.The magnitude of the probability of moving users of Gojek’s online transportation to other online transportation in Bandar Lampung City is 60% with attrition rate of 15%. Attrition rate (rate reduction) is. With a probability figure of 60% indicating that Gojek’s online transport users have a low loyalty rate (more than 50%)